Microplastic abundance, composition and distribution on selected beaches, seafloor and in marine animals of Perhentian Islands, Terengganu / Lim Ying Wei - Lim , Ying Wei (2021)
Small pieces of plastic with sizes less than 5mm is known as microplastic. Accidental intake of microplastic could disturb an organism’s digestive and hormone systems. Of all the landscapes, islands are especially vulnerable to microplastic pollution due to their distinctive geographical and meteorological characteristics. Perhentian Islands in Terengganu state of Peninsular Malaysia was chosen as the study site for microplastic research as it harbours diverse marine species and consistently receives high number of tourist arrival. This project studies microplastic abundance attached to beach and seafloor sediments, within Acropora spp. coral, and in randomly collected marine animal carcasses during both Southwest and Northeast Monsoon seasons. Overall, the distribution of microplastic did not differ much between Southwest and Northeast Monsoon seasons, with p-value more than 0.05 based on two-way ANOVA analysis. However, significant difference (p-value less than 0.05) was observed between the sampling stations, beach zones, types of microplastic (foam, fragment, line, film and pellet) and sizes of the microplastic. The distribution trend of microplastic in beach sediment, seafloor sediment, Acropora spp. and carcasses of marine animals were found to be closely related to the anthropogenic activities, on top of the oceanographic factors such as wind, water current and waves. Increased tourist arrival gave rise to escalated deposition of plastic debris on shore, as well as, elevated access to sewerage system that washed fibrous microplastic into water column. Between sampling sites, significant difference (p-value <0.05) was found in the total microplastic abundance collected from the beach sediment, primarily due to varied beach orientation, wind regime, source location, degradation process of plastic, coastal dynamic and sinking velocity of microplastic. For the type of microplastic, foam dominated in beach sediment (47-87% of total microplastic) while line occupied largest quantities in both seafloor sediment and Acropora spp.. Foam is relatively light-weighted and able to drift four times faster than fragment, line, film and pellet along the water current thus widely deposited on-shore especially at high tide zones and berm . Meanwhile, line constitutes more than 60% and 80% in both seafloor sediment and Acropora sp. respectively, owing to the input of sewerage system that washed the fibrous microplastic offshore. Apart from that, line was also the most abundant microplastic (65% of total microplastic) identified in marine animal samples (fishes, sea cucumber and squid). Most microplastic found from biological samples (Acropora spp. and animals) have the size ranging from 0.001mm to 0.09mm, which matched the normal sizes of their prey (the zooplankton). Therefore, major cause of microplastic ingestion is most likely due to properties of microplastic that highly resembled their prey, subsequently led to massive intake and retention of microplastic inside their body.